Analysis Model of Consumer Sentiment Tendency of Commodities in E-Commerce - Yao, Hui (Frontiers in Psychology, 2022)
Users are increasingly turning to the internet to acquire and consumer goods. Online purchasing builds demand between customers in modern years. E-commerce (e-commerce) is a business strategy that allows individuals and businesses to buy and sell goods and services through the Internet. Ecommerce can be used on computers, tablets, cellphones, and other smart devices, and it operates in four key market categories. The way individuals buy and consumer goods and services has changed as a result of e-commerce. People are increasingly using their computers and smart devices to place orders for things that can be delivered quickly to their homes. n the 1960s, ecommerce made use of an electronic system called electronic data interchange to help in document conversion. In the world of e-commerce, Amazon is a monster. It is, in reality, the world's largest online store, and it is still growing. As a result, it has become a significant roadblock in the retail industry, prompting some major merchants to rethink their plans and adjust their focus. This article is based on literary reviews. Developing a research framework for consumer trends, particularly in terms of purchasing behavior. The sample size for this investigation was determined using a simple rule of thumb for successful partial least squares structural equation modeling (PLS-SEM) estimation. Consumer sentiment tendencies play a major role in this research. This research's most valuable factors include a promotion, price, brand loyalty, product review, and product quality. We looked into how these aspects analyzed the customer's tendency. These are the primary topics of discussion in this study.